MEASURING CO-MOVEMENT OF REAL INTEREST RATE AND INFLATION RATE: USING VEC APPROACH - Hossain, Md. Rasel; Haque, Ahsanul; Hamja, Md. Abdullah Amir; Rana, M. Shohel (International Journal of Engineering Technologies and Management Research, 2020)
It is important to know the future movement of economic variables for the planning and development of a country, Vector Error Correction (VEC) Model has been applied to disclose hidden long run as well as short-run patterns of the selected variables. ADF unit root testing procedure was applied to satisfy the conditions of applying the VEC Model. Using Johansen cointegration test long-run cointegration has been justified. But the VEC model reveals that long run significant causal relationship between the variables whereas there is no short-run causal relationship. The parameter was estimated using the OLS estimation technique. The validity of the model was confirmed by applying different quantitative approaches such as normality test, autocorrelation test, Portmanteau test, Unit root test, and various graphical approaches which suggested model selection and estimation were correct. The result of this present study may help Govt. agencies as well as planners to take an idea.